Produção de glicose e frutose por invertase de Saccharomyces cerevisiae imobilizada em suporte MANAE-agarose - Goulart, Antonio José [UNESP]; Francisco dos Santos, Andréa [UNESP]; Tavano, Olga Luisa; César Vinueza, Julio [UNESP]; Contiero, Jonas [UNESP]; Monti, Rubens [UNESP] (My University, 2013)
Invertase from Saccharomyces cerevisiae was immobilized on agarose beads, activated with various groups (glyoxyl, MANAE or glutaraldehyde), and on some commercial epoxy supports (Eupergit and Sepabeads). Very active and stable invertase derivatives were produced by the adsorption of the enzyme on MANAE-agarose, MANAE-agarose treated with glutaraldhyde and glutaraldehyde-agarose supports. At pH 5.0, these derivatives retained full activity after 24h at 40°C and 50 °C. When assayed at 40°C and 50°C, with the pH adjusted to 7.0, the invertase-MANAE-agarose derivative treated with glutaraldehyde retained 80% of the initial activity. Recovered activities of the derivatives produced with MANAE, MANAE treated with glutaraldehyde and glutaraldehyde alone were 73.5%, 44.4% and 36.8%, respectively. These three preparations were successfully employed to produce glucose and fructose in 3 cycles of sucrose hydrolysis.
Glucose and fructose production by Saccharomyces cerevisiae invertase immobilized on MANAE-agarose support
Keywords: Glucose and fructose production; Invertase; Invertase immobilization; Saccharomyces cerevisiae; agarose; beta fructofuranosidase; epoxy resin; fructose; glucose; glutaraldehyde; sucrose; adsorption; biotechnological production; enzyme activity; enzyme assay; enzyme immobilization; enzyme stability; hydrolysis; kinetics; nonhuman; pH; temperature; thermostability